UV-blocking mica powder, cosmetics, resin compositions

JP2026165474APending Publication Date: 2026-10-14YAMAGUCHI MICA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025057879
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165474000001_ABST
    Figure 2026165474000001_ABST
Patent Text Reader

Abstract

This invention provides a UV-blocking mica powder that can impart excellent UV-blocking functionality to cosmetics, plastic materials, and the like, as well as cosmetics and resin compositions containing the same. [Solution] A mica dispersion obtained by dispersing 5 parts by weight of mica powder in 100 parts by weight of an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane is applied to a polypropylene film to a thickness of 75 micrometers and dried. When the transmittance of the coated film is measured using a spectrophotometer with a film obtained by similarly applying and drying an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane as a control, the change rate R calculated from the transmittances at 380 nm and 320 nm is in the range of 0.12 to 0.31. This ultraviolet-shielding mica powder derived from muscovite is used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ultraviolet-shielding mica powder, cosmetics, and resin compositions. More specifically, the present invention relates to an ultraviolet-shielding mica powder that exhibits greater ultraviolet shielding performance than common mica powder, and cosmetics and resin compositions containing the same.

Background Art

[0002] Mica powder has long been used for decorative purposes such as imparting scattered gloss to plaster walls and sliding door paper, but in recent years, it has been utilized as a functional powder material that imparts excellent physical properties and new functions to various industrial products. In particular, mica powder derived from muscovite is transparent and low in tinting strength particle by particle even when the aggregated powder appears white, so it causes little change in the color tone of the product when blended and is easy to add. For this reason, it is used, for example, as a functional filler for improving the physical properties of plastics and coatings used in automobiles, smartphones, and housing, as a release agent for tires and sanitary ware, or as a cosmetic raw material for improving the feel of use of foundations. However, products in which these mica powders are used share common problems related to ultraviolet rays. For example, in the case of resin compositions, ultraviolet rays directly act on polymers to break bonds and cause degradation, so it is common to add ultraviolet absorbers and the like, but high-quality ultraviolet absorbers are costly, leading to cost management issues in mass-production manufacturing industries, the risk of thermal decomposition during heat treatment at molding, and the fact that the effect of ultraviolet absorbers is limited to specific ultraviolet regions, making it difficult to achieve complete protection from all ultraviolet rays, which creates disadvantages. In the case of cosmetics, ultraviolet absorbers and ultraviolet scattering agents are similarly used to protect the skin from ultraviolet rays, but the former has safety concerns such as phototoxicity, while the latter has issues related to uniform dispersion in cosmetics due to nano-sized particles and usage restrictions on nanomaterials.

[0003] As one solution to these problems, Patent Document 1 discloses a technique to improve the lightfastness of polyphenylene ether resins by adding an ultraviolet absorber and magnesium oxide, an inorganic additive, to enhance lightfastness and reduce discoloration. However, magnesium oxide, with its high specific surface area and bulkiness, cannot be sufficiently mixed under the gentle stirring conditions of a typical extruder, resulting in non-uniformity and problems not only with improving lightfastness but also with strength.

[0004] In cosmetics, inorganic powder composites obtained by surface treatment with silicon compounds, fatty acids, and hydrated silica, such as those described in Patent Document 2, have been proposed to improve dispersibility and stability. However, even with these composite powders, problems remain, such as the need for pre-dispersion in the cosmetic manufacturing process and the increasing amount resulting in a stronger squeaky feeling characteristic of fine particles. To eliminate the need for pre-dispersion, dispersions of inorganic powders have been proposed, such as those described in Patent Documents 3 and 4, but these are not convenient raw materials for formulations due to the limitations imposed by the components contained in the raw materials during cosmetic formulation. Furthermore, since the cohesive force of the powder can be weakened and dispersibility improved by reducing the particle size to micron size, micron-sized flake-shaped titanium dioxide fine particle dispersion composite particles, such as those described in Patent Document 5, have been shown. However, in the case of such composite particles, the raw material cost becomes high due to the compounding process.

[0005] Therefore, generally speaking, in cosmetics, for example, UV absorbers such as ethylhexyl methoxycinnamate and UV scattering agents such as titanium dioxide are often used to protect the skin from ultraviolet rays. Also, in plastic materials, for example, UV absorbers such as benzotriazole organic compounds are commonly used to prevent degradation caused by ultraviolet rays. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2021-8442 [Patent Document 2] Patent Application No. 2020-553346 [Patent Document 3] Japanese Patent Publication No. 2018-24881 [Patent Document 4] Japanese Patent Publication No. 2019-167344 [Patent Document 5] Japanese Patent Publication No. 2017-114826 [Overview of the Initiative] [Problems that the invention aims to solve]

[0007] As described above, while measures have been taken to protect against ultraviolet rays in industrial products such as resin compositions and cosmetics that use mica powder, there are problems with the manufacturing process, product safety, and cost. Therefore, there has been a need for the development of functional fillers and cosmetic raw materials that have excellent UV shielding properties to solve these problems.

[0008] On the other hand, although mica powder derived from muscovite is used in cosmetics and plastic materials as described above, it has not been known until now that muscovite-derived mica powder itself has the function of shielding against ultraviolet rays. For this reason, muscovite-derived mica powder has not been used as an ultraviolet shielding agent until now. If ultraviolet shielding ability could be imparted to this commonly used muscovite-derived mica powder, it could be used to replace ultraviolet absorbers such as ethylhexyl methoxycinnamate and ultraviolet scattering agents such as titanium dioxide in cosmetics and plastic materials, thereby providing ultraviolet shielding ability that is superior in terms of safety and cost. (Note that the mica powder, mica, ultraviolet shielding mica, and natural mica described in this invention below are derived from muscovite.)

[0009] The problem that the present invention aims to solve is to provide a UV-shielding mica powder that can impart excellent UV-shielding functionality to cosmetics, plastic materials, and the like, as well as cosmetics and resin compositions containing the same. [Means for solving the problem]

[0010] The inventors of this application conducted thorough research into the above-mentioned problems and, as a result, re-examined the functionality of mica. Compared to talc, mica powder has a higher aspect ratio and modulus of elasticity and superior thermal stability. Therefore, in resin compositions, it is used to improve physical properties such as increased rigidity, prevention of warping, reduction of molding shrinkage, improved heat resistance, and vibration damping, and is blended in relatively large amounts, ranging from several weight percent to tens of weight percent. In cosmetics, it is also used in solid powder cosmetics, etc., to impart spreadability, gloss, smoothness, and transparency, and is a major component as an aggregate that forms the dosage form. In other words, mica powder is one of the main components in both, and the inventors believed that if mica could be improved by a specific method to impart UV shielding ability and be replaced, it would be possible to impart or improve UV protection to resin compositions and cosmetics while reducing manufacturing problems, product safety, and costs.

[0011] In other words, the inventors of the present invention discovered that mica powder derived from muscovite, obtained by calcining under specific heat treatment conditions, has ultraviolet shielding properties, and that this calcined mica powder is characterized by a significant decrease in light transmittance, particularly in the UV-A region with wavelengths of 320-380 nm. They confirmed that the ultraviolet shielding mica powder of the present invention can be distinguished from ordinary mica powder by the rate of change R of transmittance with respect to wavelength. Furthermore, they found that it can be processed at a cost comparable to that of general powder surface treatment, and that using this ultraviolet shielding mica powder can prevent degradation of resin compositions due to ultraviolet rays and provide ultraviolet protection in cosmetics, thus leading to the completion of the present invention.

[0012] The ultraviolet-shielding mica powder according to the present invention is composed of mica powder derived from muscovite, and the value of the rate of change R of transmittance, calculated from the following formula, is 0.12 or more and 0.31 or less. (Math 1) R = (T380 - T320) / (380 - 320) T380: Transmittance at a wavelength of 380 nm (%) T320: Transmittance at a wavelength of 320 nm (%) Provided that the transmittance is measured by a spectrophotometer using, as a control, a film obtained by coating a polypropylene film with an equal-weight mixture of trimethylsiloxysilicic acid and cyclopentasiloxane to a thickness of 75 μm and drying the same, with respect to a coated film obtained by dispersing 5 parts by weight of the mica powder in 100 parts by weight of an equal-weight mixture of trimethylsiloxysilicic acid and cyclopentasiloxane, coating a polypropylene film with the resulting dispersion to a thickness of 75 μm, and drying the coated film.

[0013] The value of the change rate R is preferably 0.19 or more and 0.31 or less. The value of the change rate R is more preferably 0.25 or more and 0.31 or less.

[0014] Further, the cosmetic according to the present invention contains the ultraviolet shielding mica powder according to the present invention.

[0015] Further, the resin composition according to the present invention contains the ultraviolet shielding mica powder according to the present invention. [Advantageous Effects of Invention]

[0016] According to the ultraviolet shielding mica powder of the present invention, an excellent ultraviolet shielding function can be imparted to cosmetics, plastic materials, and the like.

[0017] In this case, when the value of the change rate R is 0.19 or more and 0.31 or less, a more excellent ultraviolet shielding function can be imparted to cosmetics, plastic materials, and the like.

[0018] In addition, when the value of the change rate R is 0.25 or more and 0.31 or less, a further excellent ultraviolet shielding function can be imparted to cosmetics, plastic materials, and the like.

[0019] Further, the cosmetic according to the present invention contains the ultraviolet shielding mica powder according to the present invention, and thus has an excellent ultraviolet shielding function.

[0020] And, since the resin composition according to the present invention contains the ultraviolet-shielding mica powder according to the present invention, it has an excellent ultraviolet shielding function. Brief Description of the Drawings

[0021] [Figure 1] This is a representative example of the transmittance measured in the Examples and Comparative Examples. [Figure 2] This is a distribution diagram of the change rate R calculated from the transmittance measured in the Examples and Comparative Examples. [Figure 3] This is a representative example of the transmittance measured for powder foundations containing the mica powders of the Examples and Comparative Examples. [Figure 4] This is a representative example of the transmittance measured for cream foundations containing the mica powders of the Examples and Comparative Examples. Modes for Carrying Out the Invention

[0022] The ultraviolet-shielding mica powder according to the present invention will be described in detail.

[0023] The ultraviolet-shielding mica powder of the present invention is composed of muscovite-derived mica powder, and the value of the transmittance change rate R calculated from the following formula is 0.12 or more and 0.31 or less. (Equation 1) R=(T380-T320) / (380-320) T380: Transmittance (%) at a wavelength of 380 nm T320: Transmittance (%) at a wavelength of 320 nm Here, the transmittance is measured by a spectrophotometer, using as a control a film obtained by coating an equal-weight mixture of trimethylsiloxysilicic acid and cyclopentasiloxane on a polypropylene film to a thickness of 75 μm and drying the same, with respect to a coated film obtained by dispersing 5 parts by weight of the mica powder in 100 parts by weight of the equal-weight mixture of trimethylsiloxysilicic acid and cyclopentasiloxane, coating the resulting dispersion on a polypropylene film to a thickness of 75 μm, and drying the same.

[0024] The UV-shielding mica powder of the present invention tends to show a gradual decrease in transmittance (%T) toward lower wavelengths in the visible light region, similar to ordinary mica powder. However, it exhibits a sharp decrease in transmittance toward lower wavelengths, particularly around 400 nm, and especially in the 320-380 nm range, which corresponds to the UV-A region of ultraviolet light. As a result, it shows an even lower transmittance than ordinary mica powder in the UV-B region, which is below the UV-A region, exhibiting an UV-shielding effect across the entire UV region. Therefore, mica powders that show a significant decrease in transmittance in the range where the transmittance decreases linearly from around 400 nm, i.e., in the 320-380 nm range, which corresponds to the UV-A region of ultraviolet light, are identified as having a high UV-shielding effect, and are specified as UV-shielding mica powders by the rate of change of transmittance with respect to wavelength, R.

[0025] The ultraviolet-shielding mica powder in the present invention is a mica powder in which the rate of change R of transmittance with respect to wavelength is larger than that of ordinary mica powder, calculated to be at least 0.12. However, the R value is calculated in the range of 0.12 to 0.31 based on an upper limit of 0.31 set based on the mean value and standard deviation actually calculated from measured values. Considering that the ultraviolet-shielding effect is remarkable while maintaining the original crystalline structure of mica, an R of 0.19 to 0.31 is preferred, and 0.25 to 0.31 is even more preferred.

[0026] The ultraviolet-shielding mica powder of the present invention can be obtained by the following manufacturing methods to obtain a desired R value, but is not limited to these methods.

[0027] <Manufacturing method 1> First, muscovite ore, obtained in flake form with a size of approximately 2 to 8 mesh from India, China, Canada, Brazil, the United States, etc., is dry-ground using a dry grinding machine such as a hammer mill that does not use water. After passing through a sieving classification process to obtain mica powder, a calcination process is carried out to obtain the ultraviolet-shielding mica powder of the present invention.

[0028] <Manufacturing method 2> In the same manner as in Manufacturing Method 1, muscovite ore is procured, mixed with water, and wet-ground using a wet grinding machine such as a ball mill. After undergoing a classification process using a sieve or centrifuge and a drying process, mica powder is obtained, followed by a calcination process to obtain the ultraviolet-shielding mica powder of the present invention.

[0029] <Manufacturing method 3> In the same manner as in Manufacturing Method 1, muscovite ore is procured and subjected to a calcination process before crushing. The resulting calcined flake-like muscovite ore is then dry-crushed using a dry crushing machine such as a hammer mill that does not use water, and after a classification process using a sieve, the ultraviolet-shielding mica powder of the present invention is obtained.

[0030] <Manufacturing method 4> In the same manner as in Manufacturing Method 1, muscovite ore is procured and subjected to a calcination process before crushing. The resulting calcined flake-like muscovite ore is mixed with water and wet-crushed using a wet-crusting machine such as a ball mill. After undergoing a classification process using a sieve or centrifuge and a drying process, the ultraviolet-shielding mica powder of the present invention is obtained.

[0031] The muscovite used in the manufacture of the present invention is highly transparent and has excellent heat resistance, so mica plates made into sheets are used as window mica (viewing windows) for instant water heaters and kerosene stoves. Furthermore, the firing process in each manufacturing method, which involves processing at even higher temperatures, generally has the effect of removing bound water contained in the muscovite ore or mica powder crystals and expanding the layered crystalline structure.

[0032] In this invention, we have found that mica powder processed with a specific firing temperature and firing time, as well as a specific firing and grinding sequence and grinding method, shows a significant decrease in transmittance in the wavelength range of 380 nm or less, specifically in the lower wavelength range from the UV-A region. Furthermore, we have found that mica useful for UV shielding, i.e., UV-shielding mica powder, can be identified by the rate of change R of transmittance with respect to wavelength in this wavelength range, and this constitutes the present invention.

[0033] The firing temperature of the mica powder is not particularly limited, but from the viewpoint of a large rate of change R, it is preferably 600°C or higher. More preferably 700°C or higher. On the other hand, the upper limit of the firing temperature is not particularly limited, but from the viewpoint of suppressing changes in the crystal structure due to melting, etc., and having a better ultraviolet shielding effect, it is preferably 1000°C or lower. More preferably 900°C or lower. Furthermore, from the viewpoint of a large rate of change R, the firing temperature of the mica powder is more preferably 600°C to 1000°C, and particularly preferably 700°C to 900°C.

[0034] The firing time for mica powder is preferably 1 hour or more, although this depends on the firing temperature and the amount to be fired. Furthermore, from the viewpoint of suppressing uneven firing, the firing time for mica powder is preferably 3 hours or more, and more preferably 5 hours or more. On the other hand, from the viewpoint of efficiently utilizing the ultraviolet shielding function without energy waste, it is preferable to fire for 10 hours or less. Note that firing time refers to the time from reaching the target firing temperature in a batch-type firing furnace until the temperature is maintained at a constant level, and in a continuous-type firing furnace, it refers to the time the mica powder passes through the furnace at the target temperature.

[0035] Furthermore, the flake-shaped muscovite ore used in the present invention has uneven flake size, which may lead to uneven firing. For this reason, considering the uniformity of firing, among the above manufacturing methods, manufacturing methods 1 and 2, which involve firing a product that has been finished to mica powder, are preferred, and in particular, manufacturing method 2 is the most preferred, as determined from the actual R value results.

[0036] In addition, in manufacturing methods 3 and 4 of the present invention, which involve a calcination process before pulverization, an acid treatment process using sulfuric acid or nitric acid may be added after the calcination process to soften the muscovite ore and make it easier to peel into thinner layers.

[0037] The volume-average particle size (volume-average particle size obtained by a laser diffraction / scattering particle size distribution analyzer) of the UV-shielding mica powder of the present invention, as described above, is not particularly limited, and the UV-shielding effect does not change significantly depending on the particle size. However, from the viewpoint of maintaining product characteristics such as ease of incorporation into cosmetics and resins, the appearance of the cosmetic, and the design of the product, a particle size of 3 to 60 micrometers is more preferable.

[0038] As described above, the ultraviolet-shielding mica powder of the present invention is composed of mica powder derived from muscovite, and the value of the rate of change R of transmittance calculated from the following formula is between 0.12 and 0.31, thus providing excellent ultraviolet-shielding functionality to cosmetics, plastic materials, and the like.

[0039] The UV-shielding mica powder of the present invention can be added to various materials by utilizing its excellent UV-shielding function. It is particularly suitable for use in cosmetics and plastic materials.

[0040] The cosmetic composition according to the present invention (hereinafter sometimes referred to as "this cosmetic composition") contains the ultraviolet-shielding mica powder of the present invention. This cosmetic composition is suitable as a makeup cosmetic in which powder is used, or as a sunscreen agent requiring ultraviolet protection, and is not particularly limited as long as the desired feel can be obtained by containing the powder.

[0041] In makeup cosmetics, particularly powder and solid powder cosmetics, extender pigments such as talc and mica are used as the main powder ingredients and aggregates, and are present in large quantities as constituent components. Furthermore, due to the issue of asbestos in talc, the concept of talc-free cosmetics is becoming more widespread, and mica plays a significant role as a main ingredient.

[0042] Furthermore, among makeup cosmetics, emulsified cosmetics mainly consist of liquid components such as water and volatile oils, and contain few colorants to adjust the tone or extender pigments such as mica to adjust the feel and finish. However, after application, the majority of the coating film consists of powdered colorants and extender pigments, so extender pigments such as mica play a significant functional role in providing transparency and concealing fine lines on the cosmetic coating film.

[0043] In sunscreens, fine particles of titanium dioxide and zinc oxide are used as UV scattering agents, but plate-shaped mica and other materials are sometimes added to adjust the spreadability of the coating film, making them important components as well.

[0044] Furthermore, these emulsified makeup cosmetics and sunscreens often contain poorly soluble UV absorbers, such as t-butyl methoxydibenzoylmethane and diethylamino hydroxybenzoyl hexyl benzoate, to enhance their UV-A protection. However, there is a current problem where crystals of these UV absorbers tend to precipitate in the cosmetics, and the highly polar oils used to dissolve these UV absorbers can easily cause emulsification in the cosmetics.

[0045] Therefore, by replacing conventional extender pigments such as mica and talc in makeup cosmetics and sunscreens with the UV-blocking mica of the present invention, it is possible to avoid risks to emulsification stability by reducing the amount of mica powder contained in the formulation and on the coating film, as well as by reducing the amount of UV absorbers and highly polar oils in the formulation. This would allow for improved UV protection of makeup cosmetics and sunscreens, specifically by improving SPF (Sun Protection Factor) and PFA (Protection Factor of UVA) values, while expanding the range of formulations while avoiding formulation risks.

[0046] In the present invention, in order to bring out the effect of the UV-shielding mica powder of the present invention in a cosmetic composition, it is necessary to include 5% by weight or more of the UV-shielding mica powder of the present invention. Furthermore, when the cosmetic composition is a powder cosmetic or a solid powder cosmetic, a concentration of 15 to 80% by weight is preferable, and when it is an emulsified cosmetic, 8 to 20% by weight can be obtained to obtain a significant UV-shielding effect.

[0047] The ultraviolet-shielding mica powder of the present invention can be used untreated when incorporated into cosmetics, but may also be used after appropriate surface treatment. The surface treatment agent is not particularly limited as long as it is a surface treatment agent commonly used for cosmetic powders. Specific surface treatment agents include, for example, fluorine compounds, silicone compounds, metal soaps, waxes, oils and fats, hydrocarbons, and the like.

[0048] In addition to the UV-blocking mica powder of the present invention, cosmetics utilizing the UV-blocking mica powder of the present invention may appropriately contain other ingredients commonly used in cosmetics, such as water, oils and fats, waxes, hydrocarbons, fatty acids, alcohols, alkyl glyceryl ethers, esters, silicone oils, fluorinated oils, polyhydric alcohols, sugars, polymers, surfactants, humectants, UV absorbers, chelating agents, pH adjusters, antioxidants, bactericidal and preservative agents, dyes, fragrances, pigments, plasticizers, organic solvents, pharmaceuticals, animal and plant extracts, amino acids and peptides, vitamins, untreated or surface-treated cosmetic powders, etc.

[0049] The resin composition in the present invention contains the ultraviolet-shielding mica powder and resin of the present invention. The resin is a thermoplastic resin or a thermosetting resin.

[0050] Examples of the thermoplastic resins mentioned above include vinyl chloride resin, vinylidene chloride resin, vinyl acetate resin, polyvinyl alcohol, polyvinyl acetal, polystyrene, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, methacrylic resin, polyethylene, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polypropylene, fluororesin, polyamide, polyacetal, polycarbonate, polyester, polyphenylene ether, polyphenylene sulfide, polyarylate, polysulfone, polyethersulfone, and liquid crystal plastics.

[0051] Examples of the thermosetting resins mentioned above include phenolic resins, amino resins, unsaturated polyesters, vinyl ester resins, diallyl phthalate resins, epoxy resins, polyurethanes, silicon resins, and polyimides.

[0052] In the present invention, the resin composition contains 1 to 50% by weight of the UV-shielding mica powder of the present invention, similar to general fillers, and preferably 5 to 40% by weight, considering ease of mixing while obtaining a greater UV-shielding effect.

[0053] The ultraviolet-shielding mica powder of the present invention can be used untreated when incorporated into a resin composition, but may also be used after appropriate surface treatment. The surface treatment agent is not particularly limited as long as it is a surface treatment agent commonly used for fillers. Specific examples of surface treatment agents include silane coupling agents and acid-modified polymers.

[0054] The resin composition containing the ultraviolet-shielding mica powder of the present invention may optionally contain one or more of the following: antioxidants, heat stabilizers, weather resistance improvers, mold release agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, etc. Furthermore, other fillers besides the ultraviolet-shielding mica of the present invention may be included as needed. Examples of such fillers include calcium carbonate, clay, synthetic silicon, titanium dioxide, carbon black, barium sulfate, mica, glass fiber, whiskers, carbon fiber, magnesium carbonate, kaolin, graphite, molybdenum disulfide, zinc oxide, and the like.

[0055] The formulation and kneading of the ultraviolet-shielding mica powder of the present invention can be carried out using known methods that utilize commonly used short-shaft extruders, twin-shaft extruders, Banbury mixers, pressure kneaders, etc.

[0056] Although embodiments of the present invention have been described above, the present invention is not limited in any way to the above embodiments, and various modifications are possible without departing from the spirit of the present invention. [Examples]

[0057] The present invention will be described in detail below using examples and comparative examples.

[0058] <Preparation and performance evaluation of UV-shielding mica powder> Table 1 shows examples and comparative examples of the preparation of the ultraviolet-shielding mica powder of the present invention. Mica from India was used, and ultraviolet-shielding mica powder with the manufacturing method, calcination conditions, and particle size shown in Table 1 was obtained. For example, in Example 1, muscovite ore procured from India in flake form with a size of about 2 to 8 mesh was mixed with water and wet-milled in a wet mill, followed by a classification process using a sieve or centrifuge and a drying process to obtain mica powder with an average particle size of 10 micrometers. This was then placed in a crucible of about 50 g and calcined at 600°C for 1 hour to obtain the ultraviolet-shielding mica powder of the present invention.

[0059] [Table 1]

[0060] The UV-shielding mica powders of the examples and comparative examples prepared according to Table 1 were evaluated by measuring their transmittance (%T) as follows. 1) Disperse 5 parts by weight of each powder uniformly in 100 parts by weight of an equal-weight mixture of trimethylsiloxysilicate and cyclopentasiloxane to obtain a dispersion. 2) The obtained dispersion is coated onto a polypropylene film to a thickness of 75 micrometers and dried. 3) For the obtained coated films, the transmittance (%T) was measured using a spectrophotometer in the wavelength range of 280 to 800 nm, using a film obtained by similarly coating and drying an equiweight mixture of trimethylsiloxysilicate and cyclopentasiloxane as a control. All measurements were performed using a JASCO V-770 with a data acquisition interval of 1 nm, a bandwidth of 5.0 nm, a response of 0.24 sec, and a scanning speed of 400 nm / min.

[0061] A representative example measured using the above procedure is shown in Figure 1.

[0062] The mica powder shown in Comparative Example 1 is not pure white because it is a natural mineral, and therefore its transmittance gradually decreases from the higher wavelength side in the visible light region (380-800 nm). However, in the UV-shielding mica powder of Example 4, a significant decrease in transmittance is observed from the UV-A region to the UV-B region, with a bending point occurring from around 380 nm towards the lower wavelength side. It is observed that the transmittance decreases at each wavelength only in the difference region enclosed by the curves of Comparative Example 1 and Example 4, and the UV-shielding properties are enhanced. In other words, in the case of cosmetics, the larger this region is, the larger the actual SPF and PFA values ​​will be.

[0063] On the other hand, in the case of talc, which is used as a filler and cosmetic ingredient, similar to mica, as shown in Comparative Examples 6 and 7, both the uncalcined and calcined products only showed a gradual decrease across the entire wavelength range, and no characteristic decrease in transmittance was observed in the lower wavelength range from 380 nm, meaning there was no difference between the uncalcined and calcined products.

[0064] From the changes in transmittance of each powder as described above, the tendency of transmittance decrease is particularly remarkable in the wavelength range exactly corresponding to the UV-A wavelength region of 320 to 380 nm, so mica with a large rate of change was designated as the ultraviolet-shielding mica powder. That is, from the obtained transmittance (%T) values, R=(T380-T320) / (380-320) where T380: transmittance (%) at a wavelength of 380 nm T320: transmittance (%) at a wavelength of 320 nm It was determined that mica powders exhibiting this characteristic ultraviolet-shielding property can be identified by the transmittance change rate R with respect to wavelength calculated by the formula shown. The calculation results of the R values are listed in the right column of Table 1, and the distribution state of the R values is shown in Figure 2.

[0065] When the obtained distribution state of R values in Figure 2 was confirmed, it was shown that there are a group showing values near the R value of Comparative Example 1 which is unfired mica, a group showing R values of 0.12 to 0.14, a group showing large R values of 0.19 or more, and a group showing particularly large R values of 0.25 or more. Regarding the upper limit, in consideration of measurement variations, the value was set to 0.31 based on the average value and standard deviation in the measurement of Example 6.

[0066] That is, from this distribution state, the ultraviolet-shielding ability of each powder was determined within the following ranges of R values, and the results are also shown in the right column of Table 1. <R value> <Determination of ultraviolet-shielding ability> Less than 0.10 : × 0.10 or more and less than 0.19 : △ 0.19 or more and less than 0.25 : 〇 0.25 or more : ◎

[0067] From the results of Table 1 and Figure 2, it is found that even if synthetic mica or talc is fired and processed, no ultraviolet-shielding ability is exhibited, and the material that can become ultraviolet-shielding mica powder through the firing step is derived from natural mica.

[0068] Focusing on the manufacturing method, the ultraviolet shielding judgment is marked with a circle or double circle for manufacturing method 2. Comparing Examples 6, 12-14, 16, and 18, all manufactured using the same 5-hour firing time, the performance of Example 6 is remarkably superior. Therefore, the most preferred manufacturing method is manufacturing method 2, in which muscovite ore is mixed with water and wet-ground using a wet grinder such as a ball mill, followed by a classification process using a sieve or centrifuge and a drying process to obtain mica powder, and then a firing process to obtain ultraviolet-shielding mica powder.

[0069] Regarding the firing temperature, Examples 1-5 and Comparative Examples 1-3 indicate that it is necessary to perform the firing at 600-1000°C. Natural mica contains crystalline water in its crystalline structure, and the separation of crystalline water from the crystalline structure begins at approximately 550°C, which coincides with the firing temperature at which ultraviolet shielding ability begins to be exhibited (see: Yamaguchi Mica Technical Data Collection "Heat Resistance Evaluation of Firing Mica", published March 11, 2021, https: / / yamaguchi-mica.com / tech info / tech data / general / tech general 2021011101.pdf). Furthermore, firing at 1100°C not only lowers the R value but also melts the mica itself, causing it to lose its original properties, so it can be determined that this is not a firing temperature condition that achieves the present invention. In addition, from the results of the ultraviolet shielding evaluation, as mentioned above, a firing temperature of 700-900°C is even more preferable, and comparing the R values, 800°C is the most preferable.

[0070] Regarding the firing time, while the UV-shielding mica powder of the present invention was obtained in Examples 1 to 7, Examples 6 and 7 showed significantly higher values. Therefore, although firing requires at least 1 hour, it is preferable to fire for 5 to 10 hours to obtain a product with high shielding effect while minimizing uneven firing. Furthermore, firing for more than 10 hours does not increase the R value and only incurs extra firing energy and costs.

[0071] Furthermore, regarding the average particle size of the UV-shielding mica powder, it can be determined from the R values ​​of Examples 1-5 and 8-11 that the difference in R values ​​due to particle size is small.

[0072] Based on the above, the preparation method for UV-shielding mica powder and the performance evaluation of the obtained UV-shielding mica powder indicate that the UV-shielding mica powder obtained using manufacturing method 2, with a firing temperature of 800°C and a firing time of 5 to 10 hours, exhibits an R value of 0.25 or higher, demonstrating remarkable performance.

[0073] <Application to solid powder cosmetics> Using the prepared UV-blocking mica powder, Example 19 and Comparative Example 8, which are powder foundations for solid powder cosmetics, were prepared according to the formulations shown in Table 2 below.

[0074] [Table 2] <Preparation method> Ingredients 1-11 were uniformly mixed in a Henschel mixer and then ground in an atomizer. Furthermore, the mixed and ground product of ingredients 1-11 and ingredients 12 and 13 were uniformly mixed in a Henschel mixer, ground in an atomizer, passed through a sieve, and pressed into a medium dish to obtain a powder foundation.

[0075] The UV protection ability of the obtained powder foundation was evaluated using the following procedure. 1) Remove the solid powder foundation from the tray and return it to its powder form. 2) Because it contains oil as a binder and hydrophobic powder, 15 parts by weight of cyclopentasiloxane was added to 10 parts by weight of the powder foundation, which had been returned to a powder state, and pre-dispersed. 3) Next, 90 parts by weight of an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane were added and thoroughly dispersed to prepare a dispersion for coating. 4) The obtained dispersion was coated onto a polypropylene film to a thickness of 75 micrometers and dried. 5) Using the obtained coated film as a control, the transmittance (%T) was measured using a spectrophotometer in the wavelength range of 280 to 800 nm, using the same mixed solution prepared in the above steps 2) to 4) by removing the solid powder foundation, and then drying the resulting film.

[0076] Figure 3 shows the results of evaluating the UV shielding ability of the powder foundations of Example 19 and Comparative Example 8. In Figure 3, the change in transmittance in the wavelength range of 280-320 nm is also shown in magnified detail.

[0077] In the formulation of Comparative Example 8, mica was used as the extender pigment that forms the aggregate of the solid powder cosmetic. Although the mica portion of Comparative Example 1 was entirely replaced with UV-blocking mica powder, and no significant difference in hue was observed between the powder foundations of Example 19 and Comparative Example 8 (a color difference of 1.19 between Example 19 and Comparative Example 8), as shown in Figure 3, it was confirmed that Example 19 showed improved shielding effect not only in the UV region below 380 nm, but also in a wide wavelength range where the transmittance gradually decreased from the visible light region, through the blue light region, and further into the UV region below 380 nm. Therefore, it is highly significant that, not only at the level of a cosmetic raw material alone, but also in actual powder foundations, mica showed a synergistic effect with UV absorbers such as component 12 and UV scattering agents such as components 7 and 8, resulting in a significantly reduced transmittance and high UV shielding ability. These results indicate that the UV-blocking mica powder of the present invention can enhance the UV protection effect of powder foundations. In particular, a clear trend of decreasing transmittance in the 320-380 nm range was observed, suggesting that it can also be applied to formulations that enhance UV-A protection and highly prevent photoaging.

[0078] <Application to emulsified cosmetics> The prepared UV-blocking mica powder was pre-treated with 3% by weight of amodimethicone, and Example 20 and Comparative Example 9, which are water-in-oil (W / O) emulsion cosmetic cream foundations, were prepared using the formulations shown in Table 3 below. [Table 3] <Preparation method> Component 11 was heated and dissolved in component 10, and then components 12-16 and component 18 were added and homogenized to obtain an oily mixture. Next, the powders of components 1-9 were crushed and mixed, and then dispersed in the aforementioned oily mixture. A mixture of components 17 and 19 was then added to form the oil phase. Furthermore, component 21 was heated and dissolved in component 22, and then component 20 was added and added to an aqueous solution consisting of components 23 and 24 to obtain the aqueous phase. After that, the obtained oil phase and aqueous phase were mixed and uniformly stirred while applying shear to obtain a W / O type emulsified cosmetic cream foundation.

[0079] The UV protection ability of the obtained cream foundation was evaluated using the following procedure. 1) To 10 parts by weight of cream foundation, 20 parts by weight of cyclopentasiloxane was added and pre-dispersed. 2) Next, 90 parts by weight of an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane was added and thoroughly dispersed to obtain a dispersion for coating. 3) The obtained dispersion was coated onto a polypropylene film to a thickness of 75 micrometers and dried. 4) For the obtained coated films, the transmittance (%T) was measured using a spectrophotometer in the wavelength range of 280 to 800 nm, using the film obtained by similarly coating the mixed solution prepared in the same manner as in steps 1) to 3) above (excluding the cream foundation) and drying it as a control.

[0080] Figure 4 shows the results of evaluating the UV protection ability of the cream foundations in Example 20 and Comparative Example 9.

[0081] In cream foundations, unlike solid powder cosmetics, extender pigments such as mica are not added in large quantities, but they are used to adjust the feel and finish. Although the amount of mica used as an extender pigment is reduced, when ordinary mica is replaced with the UV-blocking mica powder of the present invention, it was confirmed that the transmittance of Example 20 decreased compared to Comparative Example 9, as shown in Figure 4, and the UV-blocking ability was increased. In emulsified cosmetics, poorly soluble UV absorbers such as component 11 are often added to improve UV-A blocking ability. In order to add poorly soluble raw materials, it is necessary to use a highly polar oil in the oil phase, but if used carelessly, the emulsifier is also dissolved in the oil phase, often destabilizing the emulsion. Adding an emulsifier as a countermeasure results in a sticky feel. If the amount of UV absorber can be reduced from the formulation by using UV-blocking mica powder, it may be possible to provide a cream foundation with high emulsion stability and a non-sticky feel.

[0082] <Applications to thermoplastic resins> Next, a flooring surface material with the following composition was prepared using the ultraviolet-shielding mica of the present invention. Example 21: Flooring surface material as a thermoplastic resin Ingredient name Amount (parts by weight) 1. Polyvinyl chloride resin*1 100.0 2. Plasticizer*2 50.0 3. UV-blocking mica of Example 3 20.0 (11.6% by weight in the composition) 4. Ca-Zn composite stabilizer*3 2.0 5. Benzotriazole-based UV absorber*4 0.5 *1: Manufactured by Taiyo Vinyl Co., Ltd. *2: Manufactured by J-Plus Co., Ltd. *3: Made by Adeka Corporation *4: Made by Adeka Corporation <Manufacturing method> The above components were mixed in a Banbury mixer and processed into a 0.5 mm thick sheet using a calender to create the surface sheet.

[0083] Furthermore, a 0.5 mm thick vinyl chloride resin lower layer sheet was fabricated using a vinyl chloride resin compound (manufactured by Mitsubishi Chemical Corporation) with a calender. Subsequently, the obtained surface layer sheet and three lower layer sheets from Example 18 were laminated by heat fusion to form a total of four layers.

[0084] A 3000-hour weather resistance test was conducted on a vinyl chloride resin flooring material using Example 21, employing Method A, which simulates direct outdoor exposure, in an accelerated weathering test (JIS K 7350-2) using a xenon arc light source. As a result, the vinyl chloride resin flooring material using Example 18 showed reduced deterioration of hue and other characteristics compared to the case where calcium carbonate was used as a filler instead of the UV-shielding mica powder in Example 3. By using the UV-shielding mica powder of the present invention in combination with a UV absorber, a flooring material with even higher light resistance can be provided.

[0085] <Applications to thermosetting resins> This invention provides an example of applying the UV-shielding mica powder to an epoxy resin used in printed circuit boards and the like, as a thermosetting resin. Example 22: Thermosetting composition for printed circuit boards Resin solution A was prepared with the following composition containing the ultraviolet-shielding mica powder of the present invention. Ingredient name Amount (parts by weight) 1. Polyfunctional alicyclic epoxy resin*5 120 2. UV-shielding mica powder of Example 8 20 (13.9% by weight in resin solution) 3. Wetting and dispersing agent*6 2 4. Oil compound type defoaming agent*7 2 *5: Manufactured by Daicel Corporation *6: Manufactured by BYK *7: Manufactured by Shin-Etsu Chemical Co., Ltd. <Preparation method> The above components were mixed and kneaded in a three-roll mill to prepare resin solution A.

[0086] Separately, 500 parts by weight of styrene maleic anhydride resin (manufactured by Sartomer) and 500 parts by weight of butyl carbitol acetate (manufactured by Sankyo Chemical Co., Ltd.) were placed in a reaction vessel equipped with a reflux column and heated and dissolved at 120°C for 3 hours with stirring to prepare resin solution B with a non-volatile content of 50% by weight.

[0087] The obtained resin solutions A and B were mixed in a 2:1 weight ratio, a glass slide was immersed in the mixture and withdrawn, and the resulting dip-coated sample was heat-cured at 150°C for 60 minutes to obtain a test sample of a thermosetting composition for printed circuit boards (the coating film of the test sample contained 9.3% by weight of UV-shielding mica powder).

[0088] For the evaluation, a comparative test sample was prepared by replacing the UV-shielding mica powder as a filler in component 2 with fine silica powder. This sample was placed in a 200 mL UM sample bottle (mayonnaise bottle) along with the test sample from Example 22, and the aforementioned accelerated weathering test was performed for 20 hours using a xenon arc light source. As a result, visual inspection of discoloration showed that the test sample from Example 22 showed less discoloration and superior light resistance compared to the comparative test sample. Therefore, by using the UV-shielding mica powder of the present invention, it is possible to not only impart heat resistance to resins as a filler, but also to add a new function of light resistance to home appliances and their internal printed circuit boards, where the number of light sources such as LEDs has increased and light resistance performance is increasingly required.

[0089] Although embodiments and examples of the present invention have been described above, the present invention is not limited in any way to the above embodiments and examples, and various modifications are possible without departing from the spirit of the present invention. [Industrial applicability]

[0090] The UV-shielding mica powder of the present invention can solve the problems associated with UV shielding in cosmetics and resin compositions. For example, in cosmetics, replacing powders commonly used as extender pigments with the UV-shielding mica of the present invention can enhance SPF and PFA values, thereby expanding the range of cosmetic formulations. In resin products, fillers have been attracting attention for improving resin properties, but the addition of lightfastness as a function can be expected to enhance the functionality of composite resin products.

Claims

1. A mica powder that blocks ultraviolet rays, composed of muscovite-derived mica powder, wherein the value of the rate of change R of transmittance, calculated from the following formula, is between 0.12 and 0.

31. (Math 1) R=(T380-T320) / (380-320) T380: Transmittance at a wavelength of 380 nm (%) T320: Transmittance at a wavelength of 320 nm (%) However, the transmittance is measured by spectrophotometer using a coated film obtained by coating a polypropylene film with a dispersion obtained by dispersing 5 parts by weight of the mica powder in 100 parts by weight of an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane to a thickness of 75 μm and drying the dispersion to a thickness of 75 μm, with a control film obtained by coating a polypropylene film with an equimassive mixture of trimethylsiloxysilicate and cyclopentasiloxane to a thickness of 75 μm and drying the film.

2. The ultraviolet-shielding mica powder according to claim 1, wherein the value of the rate of change R is 0.19 or more and 0.31 or less.

3. The ultraviolet-shielding mica powder according to claim 1, wherein the value of the rate of change R is 0.25 or more and 0.31 or less.

4. A cosmetic composition containing the ultraviolet-shielding mica powder described in claim 1 or claim 2.

5. A resin composition containing the ultraviolet-shielding mica powder according to claim 1 or claim 2.

Citation Information

Patent Citations

  • Composite particles in which titanium dioxide microparticles are dispersed, and cosmetic

    JP2017114826A

  • Water dispersion

    JP2018024881A

  • Dispersion

    JP2019167344A

  • Spherical composite powder for cosmetics and method for producing the same

    JP2021008442A

  • Inorganic powder composite and its manufacturing method, water-in-oil emulsion composition, and sunscreen cosmetic

    JP7311531B2